A SYSTEMATIC FAILURE OF PUBLIC POLICY IN INDIA - Choudhary, Deepshikha (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Public Policy is whatever a government does or doesn’t. Any country’s development or the lack of it is directly correlated to its public policy. This fact is understood by every political party coming to power. Yet, India hasn’t reached that stage of development that it was expected to after nearly 75 years of independence. This research paper endeavours to identify the various reasons behind this failure which looks more systematic than incidental